IMPLEMENTASI METODE MENGHAFAL QUR'AN 3T+1M DALAM MENINGKATKAN KUALITAS HAFALAN SANTRI - Tika Kusumastuti; Mukhlis Fatkhurrohman; Muhammad Fatchurrohman (Al'Ulum Jurnal Pendidikan Islam, 2022)
This study aims to determine the implementation of the Tasmi'/Talqin, Tafahum, Tikrar, and Muraja'ah (3T+1M) methods in learning to memorize the Qur'an. The type of research used is descriptive qualitative research. The subject of this research is the Tahfidz Al-Qur'an House of Amal Syuhada Gajahan Pasar Kliwon Surakarta. With data collection techniques using observation, interviews and documentation. While the data analysis used to describe the research results are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the 3t + 1M method is through the planning, implementation and evaluation process by showing the results that many students have improved memorization, quality and are in accordance with the targets set by the management and the Ustadz/ustadzah.